Refleksi diri menurut anthony giddens pada era kemajuan teknologi digital - widhi, hikmah aulia anugrah; Yovieanti, Hanin Hazivah; Al fawwazah, Fadhillah Rizqina (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has now grown increasingly rapidly, transforming nearly every aspect of social life, creating an era of homo digitalis where humans continuously interact with smart devices, social media, and the uncontrolled flow of information. In the context of this social development, self-reflection is necessary as a crucial element that enables individuals to understand themselves, assess experiences, and consciously direct behavior. Anthony Giddens' theory is suitable for analysis, through the framework of reflective modernity. This reflective modernity emphasizes reflectivity as a routine practice for constructing, evaluating, and negotiating self-identity in this increasingly rapid social change. Digital technology is not only used to facilitate access to information but also encourages a more dynamic self-awareness, despite the risk of trapping individuals in identity illusions such as algorithmic, hoaxes, and online validation. Challenges faced include the increasing spread of hoaxes, the spread of negative content, and the formation of pseudo-identities influenced by online validation. In situations like this, self-reflection, according to Giddens, functions as an important mechanism for maintaining identity stability, increasing self-awareness, and helping individuals negotiate the meaning of life amidst digital incongruities.